Influence of cell bioenergetics on host-pathogen interaction in the lung - Lohia, Gaurav Kumar; Riquelme, Sebastián A. (Frontiers in Immunology, 2025)
Pulmonary diseases, arising from infections caused by bacteria, fungi, and viruses, or stemming from underlying genetic factors are one of the leading causes of mortality in humans, accounting for millions of deaths every year. At the onset of pulmonary diseases, crucial roles are played by phagocytic immune cells, particularly tissue-resident macrophages, in regulating the immune response at the mucosal barrier. Recent strides have illuminated the pivotal role of host bioenergetics modulated by metabolites derived from both pathogens and hosts in influencing the pathophysiology of major organs. Their influence extends to processes such as the infiltration of immune cells, activation of macrophages, and the polarization phenomenon. Furthermore, host-derived metabolites, such as itaconate, contribute to the promotion of anti-inflammatory responses, thereby preventing immunopathology and facilitating the preservation of mucosal niches to thrive for the long-term. This review explores recent advancements in the field of immunometabolism, with a particular emphasis on the intricacies of disease progression in pulmonary infections caused by bacteria such as P. aeruginosa, M. tuberculosis and S. aureus and fungi like C. albicans.